Сlinical case: From appendicitis to suicide - Romaniv, Olexandr; Pohoriliak, Katherine; Ustyugova, Margaret (Psychosomatic Medicine and General Practice, 2017)
For retrospective WHO estimates more and more groups of diseases related to psychosomatic diseases. The clinical case shows the development of psychosomatic diseases and circulation accent patient experiences between somatic and mental suffering, which seriously affects the quality of life and prognosis of health.